2020
DOI: 10.1007/s00259-020-05019-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of extra-parenchymal lung involvement in asymptomatic cancer patients with COVID-19 pneumonia detected on 18F-FDG PET-CT studies

Abstract: Background Lung involvement in patients with coronavirus disease 2019 (COVID-19) undergoing PET-CT has been previously reported. However, FDG uptake outside lung parenchyma was poorly characterized in detail. We evaluated the extraparenchymal lung involvement in asymptomatic cancer patients with COVID-19 pneumonia through 18 F-FDG PET-CT. Methods A total of 1079 oncologic 18 F-FDG PET-CT were performed between February 2 and May 18, 2020. Confirmed COVID-19 pneumonia was defined as characteristic ground-glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…One study found that 2-[ 18 F]FDG uptake of pulmonary CT abnormalities, in particular in cases of consolidation areas, were significantly lower in patients with a final diagnosis of COVID-19 compared to those who were negative for COVID-19 [8]. Conversely, another study did not find a significant difference of 2-[ 18 F]FDG uptake in ground glass pulmonary infiltrates between COVID-19 patients and controls [17]. Some studies reported that the prevalence of incidental pulmonary findings suspicious for interstitial pneumonia by COVID-19 at 2-[ 18 F]FDG PET/CT was higher when compared to 2-[ 18 F]FDG PET/CT scans of the same period one year earlier, without significant differences in 2-[ 18 F]FDG uptake [7,12,13,16].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study found that 2-[ 18 F]FDG uptake of pulmonary CT abnormalities, in particular in cases of consolidation areas, were significantly lower in patients with a final diagnosis of COVID-19 compared to those who were negative for COVID-19 [8]. Conversely, another study did not find a significant difference of 2-[ 18 F]FDG uptake in ground glass pulmonary infiltrates between COVID-19 patients and controls [17]. Some studies reported that the prevalence of incidental pulmonary findings suspicious for interstitial pneumonia by COVID-19 at 2-[ 18 F]FDG PET/CT was higher when compared to 2-[ 18 F]FDG PET/CT scans of the same period one year earlier, without significant differences in 2-[ 18 F]FDG uptake [7,12,13,16].…”
Section: Resultsmentioning
confidence: 99%
“…From the comprehensive computer literature search of PubMed/MEDLINE and Cochrane databases, 169 records were screened. In total, 11 studies were selected and retrieved in full-text version according to the predefined inclusion criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Conversely, 158 records were excluded because case reports or small case series ( n = 51), reviews, editorials, letters ( n = 39) or because they were outside the field of interest of this review ( n = 68).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations